2018
DOI: 10.1186/s12890-018-0575-y
|View full text |Cite
|
Sign up to set email alerts
|

Disease progression in idiopathic pulmonary fibrosis with mild physiological impairment: analysis from the Australian IPF registry

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a progressive and fatal fibrosing lung disease of unknown cause. The advent of anti-fibrotic medications known to slow disease progression has revolutionised IPF management in recent years. However, little is known about the natural history of IPF patients with mild physiological impairment. We aimed to assess the natural history of these patients using data from the Australian IPF Registry (AIPFR).MethodsUsing our cohort of real-world IPF patients, we compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
62
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 21 publications
(30 reference statements)
8
62
1
Order By: Relevance
“…In our analyses, HRQL at baseline, assessed using the SGRQ total score, was worse in patients in the INSTAGE trial than in the INPULSIS trials. Previous studies have also shown that patients with IPF who have more advanced disease based on % predicted values for FVC and/or DLco have worse symptoms, worse exercise capacity, and worse HRQL [27][28][29]. In both the INPUL-SIS and INSTAGE trials, changes in SGRQ total score over 24 weeks were small, consistent with previous studies showing that small changes in FVC are not associated with meaningful changes in the patient-reported outcomes commonly used in patients with IPF [30,31].…”
Section: Discussionsupporting
confidence: 81%
“…In our analyses, HRQL at baseline, assessed using the SGRQ total score, was worse in patients in the INSTAGE trial than in the INPULSIS trials. Previous studies have also shown that patients with IPF who have more advanced disease based on % predicted values for FVC and/or DLco have worse symptoms, worse exercise capacity, and worse HRQL [27][28][29]. In both the INPUL-SIS and INSTAGE trials, changes in SGRQ total score over 24 weeks were small, consistent with previous studies showing that small changes in FVC are not associated with meaningful changes in the patient-reported outcomes commonly used in patients with IPF [30,31].…”
Section: Discussionsupporting
confidence: 81%
“…The often arbitrary percentage predicted value that divides ‘normal’ and ‘abnormal’ or stages of disease are now questionable as they can easily be altered by using a different reference equation; it is highly likely that certain equations will show better and worse predicted values in one disease and not another, leading to a question of which equation is ‘best’. Despite the differences demonstrated between equations, none performed substantially better than any other in predicting mortality; however, we did demonstrate that TLco better predicts all‐cause survival than FVC and FEV 1 /FVC …”
Section: Discussioncontrasting
confidence: 61%
“…Despite the differences demonstrated between equations, none performed substantially better than any other in predicting mortality; however, we did demonstrate that TLco better predicts all-cause survival than FVC and FEV 1 /FVC. 22,40 As a result of this work, we developed an automated reference table whereby a patient's demographics can be inserted and the %predicted values will be calculated for the reference equations included in this paper (Supplementary Information). This is not an exhaustive list; however, it may be useful for clinicians who treat IPF in a Caucasian population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations